2013
DOI: 10.1179/1743278213y.0000000095
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of X52 pipeline steel in high H2S concentration solutions at temperatures ranging from 25°C to 140°C

Abstract: High temperature and high pressure immersion tests in an autoclave were employed to study the corrosion behaviour of X52 pipeline steel in aqueous solutions containing high concentrations of H 2 S. The corrosion products generated were characterised using scanning electron microscope, energy dispersive spectroscopy and X-ray diffraction. It was seen that at a constant H 2 S concentration of 22 g/l, the corrosion rate increased with increasing temperature up to 90uC, thereafter decreased at 120uC and slightly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The dissolved Fe 2+ quickly reacted with H 2 S to form a ferric sulfide precipitant, which exhibited poor catalytic activity (eq ). To confirm this speculation, we added an AgNO 3 solution to the supernatant of MoS 2 /FeS suspension at pH 3.2 and then studied the UV–vis spectrum (Figure b). Upon mixing, a broad peak assigned to Ag 2 S NPs was observed at 252 nm, and this clearly indicated that H 2 S was released and reacted with Ag + .…”
Section: Results and Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The dissolved Fe 2+ quickly reacted with H 2 S to form a ferric sulfide precipitant, which exhibited poor catalytic activity (eq ). To confirm this speculation, we added an AgNO 3 solution to the supernatant of MoS 2 /FeS suspension at pH 3.2 and then studied the UV–vis spectrum (Figure b). Upon mixing, a broad peak assigned to Ag 2 S NPs was observed at 252 nm, and this clearly indicated that H 2 S was released and reacted with Ag + .…”
Section: Results and Discussionmentioning
confidence: 93%
“…The solution color quickly turned from light-green to black within 2 min (inset of Figure b), which confirmed that a chemical reaction was taking place. Considering that only FeCl 2 ·4H 2 O and H 2 S were present in the solution, it is reasonable to infer ferric sulfide formation. According to the above investigation, the optimal condition was found to be 5.0 mg of catalyst, 10 mg/L RhB, 20 mM H 2 O 2 , and pH 6.5. The degradation efficiency of various catalysts under the optimal condition was further investigated (Figure ). In the presence of H 2 O 2 but the absence of catalysts, the degradation efficiency was negligible, suggesting that the catalysts were essential for the activation of H 2 O 2 .…”
Section: Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…under this condition. 20 Conclusions 1. In a CO 2 dominated corrosion environment, a trace amount of H 2 S (,40 mbar, pH 2 S/pCO 2 ,1 : 100) will decrease the CO 2 corrosion rate in 3%Cr steel and the steel surface became better as well.…”
Section: Water Chemistry Analysismentioning
confidence: 99%